A 3E water energy nexus based optimum design for a hybrid PV-PEMFC electricity production systems for off-gird applications. (1st September 2022) - Shahverdian, Mohammad Hassan; Sohani, Ali; Sayyaadi, Hoseyn
Highlights: Using the optimum design is accompanied by 18.32% growth in energy production. 24.69% reduction in the water foot print function is observed. The investment returns in 4.765 years. Levelized cost of electricity is 0.2917 $. (kWh) −1, which is lower than rivals. Abstract: This study investigates a hybrid system which is composed of photovoltaic (PV) modules, electrolyzer, and polymer electrolyte membrane fuel cell (PEMFC) for electricity production in off-grid application. In the proposed system, PV modules generate power during the day. When there is a surplus in PV production, hydrogen is produced by means of an electrolyzer, and then, it is stored in a hydrogen tank using a compressor. In the cases there is a deficit, the stored hydrogen goes into the PEMFC and supplies the extra needed load. By considering number of modules, as well as the volume and pressure of H2 storage as decision variables, the system is optimized to enjoy the best possible performance. Optimization is done by taking economic, environmental, and energy (3E) indicators, while water foot print to describe the water-energy nexus is also taken into account as another objective function. Feasibility study of the system was done for a location in Iran, as one of the developing countries in the world with a huge rural population, with a comprehensive technical and economic assessment. According to the results, 18.32 and 24.69% improvement in energy production and water foot print of system compared to the base case are seen, respectively. Moreover, the levelized cost of electricity (LCOE) is 0.2917 $.(kWh) −1 . It is much lower than other rivals for electrification in rural regions. This point, in addition to having a payback period of 4.765 years has proven that the system was taken into account as an economically justifiable item.